Sexing the Cranium from the Foramen Magnum Using Discriminant Analysis in a Brazilian Sample - Lopez-Capp,Thais Torralbo (2018)
Abstract In the identification process, the foramen magnum has shown controversial results in sex estimation. The present study aimed to analyze the morphometric variables of the foramen magnum in Brazilian adult cranium for sex estimation. The sample was composed of 100 craniums (53 males and 47 females) from the documented collection of the Institute of Teaching and Research in Forensic Sciences. The protocol measurement was constituted of two linear measurements: maximum length of the foramen magnum and maximum breadth of the foramen magnum and two formulas to calculate the area, method one (M1) and method two (M2). Descriptive statistics showed statistically significant differences between sex (p<0.05) for all variables. The univariate discriminant functions showed an accuracy between 56.0-62.0%, and the multivariate analysis showed a percentage of accuracy between 60.0-65.0%, the greatest accuracy was found combining the two linear measurements with M1(71.7%), even after cross-validation (66%). Receiver Operating Characteristic (ROC) curve analysis showed that M2 is the best parameter for estimating sex (AUC=0.693). A reference table for Brazilians using the foramen magnum parameters was developed based on the results of the ROC curve analysis. In conclusion, the foramen magnum should be used with caution to estimate sex in forensic cases of fragmentary craniums, due to the limited accuracy.